How Do Electoral Rules Shape Party Structures, Government Coalitions, and Economic Policies? - Torsten Persson; Gerard Roland; Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2004)
We present a theoretical model of a parliamentary democracy, where party structures, government coalitions and fiscal policies are endogenously determined. The model predicts that, relative to proportional elections, majoritarian elections reduce government spending because they reduce party fragmentation and, therefore, the incidence of coalition governments. Party fragmentation can persist under majoritarian rule if party supporters are unevenly distributed across electoral districts. Economic and political data, from up to 50 post-war parliamentary democracies, strongly support our joint predictions from the electoral rule, to the party system, to the type of government, and to government spending.
Keywords: 330; electoral rules; party systems; coalition governments; fiscal policy; electoral accountability